New method for synthesizing high-viscosity salt-tolerant sodium polyacrylate thickening agent and preparation of three-in-one thickening agent
By using UV -optical curing technology and sodium sodium sulfate in sodium -lipidite thickening agent, prepare high viscosity and salt resistant thickeners, and combined with moisturizing agents to form a tri -in -one thickener, solving the existing thicker agent in the The problem of failure in the salt environment has achieved a wider range of application and simplified preparation process.
Patent Information
- Application Number
- CN202411491378.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing sodium polyacrylate thickeners have greatly reduced their thickening ability when encountering salts, and even failed, making it difficult to meet the needs of high viscosity and salt resistance.
Using UV optical curing technology, add a small amount of sodium sodium sulfate (NA2SO3) as a reducing agent to prepare sodium polyacrylate thickeners with high viscosity and high salt ability, and introduce moisturizing agents on this basis to form a triple -in -one thickened agent Essence
With the case that does not change the basic formula, the three -in -one thickening agent that prepares high viscosity, salt tolerance and moisturizing functions, broaden its application range, and simplify the preparation process.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and specifically synthesizes a sodium polyacrylate thickener with high viscosity and strong salt resistance through a novel and simple method, and further prepares a three-in-one thickener with high viscosity, salt resistance and moisturizing functions on this basis. Background Art
[0002] Thickeners are of various types and widely used. Among them, synthetic polymer thickeners are the most widely used and have the largest sales volume. Among synthetic polymer thickeners, polyacrylic acid thickeners are the most widely used. Since it is an anionic polyelectrolyte, it is particularly sensitive to electrolyte salts. Once it encounters salts, its thickening ability will be greatly reduced, and in severe cases it will even fail. Therefore, the study of salt-resistant sodium polyacrylate thickeners has become a hot topic. In summary, there are several methods to improve the salt resistance of thickeners. The first method is to introduce additives with certain salt resistance into the thickener formula as active monomers, so that it can be copolymerized with sodium acrylate to improve its salt resistance. For example, non-ionic monomers (acrylamide, N-vinyl pyrrolidone, etc.) are introduced. Since they are insensitive to electrolyte salts, their addition can improve the salt resistance of sodium polyacrylate thickeners. Another additive is a sulfonate monomer with strong salt resistance, such as 2-acrylamide-2-methylpropane sulfonic acid (AMPS). Because it contains macromolecular sulfonic acid groups and active double bonds, it can be copolymerized with sodium acrylate, bringing macromolecular sulfonic acid groups that are insensitive to salt into sodium polyacrylate molecules, thereby improving its salt resistance. The second method is to introduce a small amount of hydrophobic groups into hydrophilic sodium polyacrylate molecules to form a hydrophobic associating thickener. When it is dissolved in water, the hydrophobic groups are repelled by water molecules and aggregate. This aggregation can occur within the molecule - intramolecular association, or between molecules (when there are enough molecules).
[0003] ——Intermolecular association. Once the molecules are associated, a dynamic physical cross-linking network will be formed in the whole system, and the viscosity will be greatly increased. The addition of electrolytes will enhance the polarity of the aqueous solution, and the association between the molecules will also be strengthened;
[0004] The cross-linked network will also increase, and the viscosity will increase and may even be higher than the viscosity without adding electrolyte. The author introduced tetradecyl methacrylate and hexadecyl methacrylate into the sodium acrylate solution, and used the micellar copolymerization method and ultraviolet light to initiate their copolymerization to form a hydrophobically associating sodium polyacrylate thickener, which was published in the following two papers "Synthesis and Performance Study of a Hydrophobically Associating Sodium Acrylate Thickener" and "Synthesis and Performance Study of a Tetradecyl Methacrylate Hydrophobically Associating Sodium Acrylate Thickener". The third method is to increase the hydrophilicity of the thickener. The hydrophobic monomer introduced above is fatty alcohol methacrylate. Because of its poor water solubility, a highly hydrophilic polyoxyethylene ether group - (CH2-CH2-O) can be introduced into it. n Synthesized fatty alcohol polyoxyethylene ether (meth) acrylate additives RO-(CH2-CH2-O) n -CO-CH=CH2, so that the long carbon chain hydrophobic group R can be introduced, and the hydrophilic group -(CH2-CH2-O) can also be introduced at the same time n , if the degree of polymerization is increased, its hydrophilicity can be increased, and it contains double chains and is easy to copolymerize with sodium acrylate. The author copolymerized fatty alcohol (containing 16-18 carbon chain length) polyoxyethylene ether (polymerization degree n=25) methacrylate with sodium acrylate under ultraviolet light to obtain a sodium polyacrylate thickener with high viscosity and high salt resistance, and described it in detail in the paper "Study on the hydrophobic association of fatty alcohol polyoxyethylene ether methacrylate on sodium acrylate thickener". The fourth method is to synthesize amphoteric polymers, which include neutral amphoteric polymers and polymers with positive and negative charges on the molecular chain. In pure water, the electrostatic attraction of positive and negative charges in the molecule cancels each other, causing the entire molecule to shrink into a chain cluster, reducing the water volume and reducing the viscosity; once electrolyte salt is added, positive and negative ions are ionized in water and adsorbed on the negative and positive charge chains in the amphoteric polymer to shield them, thereby enhancing the interaction between them and water molecules, stretching the molecular chain, and increasing the viscosity, showing obvious "anti-polyelectrolyte" behavior.
[0005] In summary, the first three methods of improving the salt tolerance of thickeners are to add modified additives to modify the base thickener, while the fourth method is to change the monomer of the thickener to synthesize an amphoteric polymer with a special structure. However, the above methods are relatively complicated and the preparation is cumbersome, which is not conducive to further promotion. Summary of the invention
[0006] In view of the above problems, the present invention discloses a new method for synthesizing a highly viscous and salt-resistant sodium polyacrylate thickener and a three-in-one thickener preparation method thereof. Without changing the basic formula of the sodium polyacrylate thickener and without synthesizing another monomer with a special structure, UV light curing technology is adopted, but instead of adding a commonly used UV photoinitiator, a small amount of reducing agent sodium sulfite (Na2SO3) is added to prepare a sodium polyacrylate thickener with good salt resistance and high viscosity. This is a simple and easy new method.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A new method for synthesizing a high-viscosity and salt-resistant sodium polyacrylate thickener comprises the following steps: weighing a certain amount of acrylic acid from which an inhibitor has been removed, adding a certain amount of pure water, then neutralizing with a certain concentration of NaOH solution, slowly dripping it therein, keeping the temperature below 40°C, preparing a sodium acrylate neutralization solution with a neutralization degree of 80% and a solid content of 20% to 45%, then adding sodium sulfite (Na2SO3), using UV light initiation technology, and performing a polymerization reaction under ultraviolet light irradiation, thereby obtaining a high-viscosity and salt-resistant sodium polyacrylate thickener.
[0009] The invention discloses a high-viscosity and salt-resistant sodium polyacrylate thickener, which is prepared by the method.
[0010] On this basis, in order to increase the multifunctionality of the thickener, a moisturizer is further introduced. The present invention discloses a preparation method of a three-in-one thickener with high viscosity, high salt resistance and moisturizing ability, comprising the following steps:
[0011] S1. The above-prepared alkaline neutralization solution having a neutralization degree of 80%, a solid content of 20% to 45%, and containing Na2SO3 as the basis; then xanthan gum, pregelatinized potato starch, one of hydroxyethyl cellulose or trehalose are added to configure a three-in-one sodium acrylate neutralization solution;
[0012] S2. When the alkaline sodium acrylate neutralization solution starts to turn turbid from transparent, take it out and place it directly under a high-pressure mercury lamp, and adjust the distance between the mercury lamp and the sample from far to near until the reaction is completed after 2 hours to obtain a transparent gel-like three-in-one product, which is chopped into a 0.2wt% aqueous solution or further granulated, dried at 85°C to constant weight, and then crushed and sieved through 100 mesh or more to obtain a white product, which is the three-in-one thickener.
[0013] Furthermore, the amount of Na2SO3 added (calculated on a monomer basis) is 0.1-8.0 wt%, preferably 0.5-5.0 wt%.
[0014] Furthermore, the added amount of the xanthan gum, pregelatinized potato starch, hydroxyethyl cellulose or trehalose (calculated on a monomer basis) is 0.2-5.0 wt %, preferably 0.5%-3.0 wt %.
[0015] The present invention also discloses a three-in-one thickener, which is prepared by any of the methods described above.
[0016] Compared with the existing technology, the present invention has the following advantages and beneficial effects:
[0017] This study synthesized a sodium polyacrylate thickener with high viscosity and high salt resistance using an alternative method. Although light curing technology was used, the commonly used UV light curing agent and heat curing agent were not used. Instead, sodium sulfite (Na2SO3) was used, which has no absorption peak for ultraviolet light. Usually, sodium sulfite is used as a reducing agent in an oxidation-reduction initiator system. It undergoes oxidation / reduction reaction with peroxide to release active groups, so that sodium acrylate can be polymerized at a lower temperature. Alternatively, it can be used as a chain transfer agent to make the polymerization reaction more gentle. After extensive screening, we used it as a single initiator to polymerize sodium acrylate under the action of ultraviolet light to form a thickener with a slightly cross-linked structure. This structure shows an obvious "climbing rod phenomenon" when stirring in its aqueous solution on a macroscopic scale, that is, the central liquid level climbs up along the stirring rod during stirring, while the peripheral liquid level drops, which is a typical feature of viscoelastic fluids. This lightly cross-linked thickener forms a soft network in its aqueous solution, which not only increases the viscosity of the solution, but also protects the negatively charged carboxyl groups of sodium acrylate from or reduces the Na+ ions of the sodium salt. + The strength of the network structure depends on the strength of the cross-linking, and the strength of the cross-linking is affected by the amount of Na2SO3 added. If the amount added is too little, the cross-linking structure cannot be formed, and it is only sticky but not elastic, and it does not have a salt resistance effect; if the amount added is too much, the cross-linking network is too strong and too elastic, and the solubility in the solution is reduced, and swelling occurs. Therefore, it is particularly important to find the appropriate amount of Na2SO3 added, the intensity of ultraviolet light, and the time.
[0018] In addition, an additive with good moisture retention performance is introduced on the basis of the high-viscosity salt-resistant sodium polyacrylate thickener to make it a three-in-one thickener. It should be known that not all additives with moisture retention performance can be used, because the addition of some additives will affect the progress of the polymerization reaction, and some will reduce the viscosity of the product, or reduce or even eliminate its salt resistance. Therefore, it is necessary to screen out some suitable additives with good moisture retention performance and find out their optimal addition amount, because too much addition will reduce the viscosity and anti-inflammatory properties of the product, and too little addition will not have a moisturizing effect, so an intermediate balance value is to be found. The present invention adopts a simple and easy new method to synthesize a highly viscous, salt-resistant sodium polyacrylate thickener, and on this basis, a humectant is introduced to prepare a high-viscosity, salt-resistant and moisturizing three-in-one sodium polyacrylate thickener, thereby widening its scope of application. DETAILED DESCRIPTION
[0019] The technical solution of the present invention:
[0020] The first step is to synthesize a highly viscous and salt-resistant sodium polyacrylate thickener. First, the base glue is selected as a sodium acrylate neutralization solution with a neutralization degree of 80% and a solid content of 20% to 45%. Then, four samples are added with Na2SO3 in the amounts of 0% (sample 0), 0.6% (sample a), 2.6% (sample b) and 5.2% (sample c). The percentage of Na2SO3 added is based on the monomer amount. The addition amount of 0% is the control sample. No Na2SO3 is added, but 2.6 parts per thousand (monomer basis) of ultraviolet light initiator is added instead. The polymerization reaction is carried out at a certain distance from the high-pressure pump lamp to obtain a transparent gel-like product, which is prepared into an aqueous solution with a solid content of 0.2%. The viscosity η (measured using an NPJ-1 rotary viscometer with a rotation speed of 6 rpm) and its salt resistance (expressed as the viscosity retention rate μ% when the addition of NaCl is 0.15%-neutralization solution as the basis) are measured. The data obtained are as follows:
[0021] Table 1 Effect of Na2SO3 addition on viscosity of 0.2% thickener aqueous solution
[0022]
[0023] Table 2 Effect of Na2SO3 addition on viscosity retention μ% of 0.2% thickener aqueous solution (NaCl addition is 0.15% - based on neutralization solution)
[0024]
[0025] From the data in the table, it can be seen that the products obtained by UV light polymerization with the addition of Na2SO3 have high viscosity and high salt resistance, which is superior to the commercially available sodium polyacrylate thickener. The best amount of Na2SO3 added is 0.6%, and above this value, both η and μ% values have a slow downward trend, which is the result of excessive Na2SO3 acting as a chain transfer agent.
[0026] In the second step, based on the high viscosity and salt-resistant thickener, additives with good moisturizing properties were introduced, and their water retention rate was used as a measure of moisturizing performance. Four additives with better performance were screened out through measurement: xanthan gum, pregelatinized potato starch, hydroxyethyl cellulose and trehalose, and their appropriate addition amount of 0.5%-3.0% was found to synthesize a three-in-one sodium polyacrylate thickener with high viscosity, salt-resistant and moisturizing properties.
[0027] If it is a commercial product, the gel-like three-in-one sodium polyacrylate thickener can be further processed by cutting it into small particles, then drying it in an oven at 85°C to constant weight, crushing it and sieving it to a size of more than 100 mesh to obtain a white powder, and packaging it.
[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0029] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0030] Example 1
[0031] The first step is to prepare the basic neutralizing solution. Weigh a certain amount of acrylic acid from which the inhibitor has been removed, add a certain amount of pure water, and then neutralize it with a certain concentration of caustic soda (NaOH) solution, slowly add it dropwise, keep the temperature below 40°C, and prepare a sodium acrylate neutralizing solution with a neutralization degree of 80% and a solid content of 20% to 45% as the basic solution.
[0032] The second step is to weigh 100g of the above basic neutralization solution and add 1.2g of 20% Na2SO3 aqueous solution.
[0033] Stir thoroughly and evenly, then add 5.0 g of 10% concentration xanthan gum solution (prepare it overnight to allow it to fully dissolve), and stir evenly to prepare a three-in-one sodium acrylate neutralization solution with a Na2SO3 content of 0.63% (monomer basis) and a xanthan gum content of 1.3% (monomer basis).
[0034] The third step, when the above neutralized solution begins to turn turbid from transparent, take it out and place it directly under a high-pressure mercury lamp, and adjust the distance between the mercury lamp and the sample from far to near. After the reaction is completed, a transparent gel-like three-in-one product is obtained, which is chopped into a 0.2% concentration aqueous solution, and then its viscosity η, viscosity retention rate μ% and water retention rate P% are measured. The obtained data are listed in Table 3.
[0035] Example 2
[0036] Weigh 100g of the above basic neutralizing solution, add 1.9g of 20% Na2SO3 aqueous solution, stir evenly, then add 5.0g of 10% potato pregelatinized starch aqueous solution (prepare overnight to allow it to swell fully), stir evenly, and a three-in-one sodium acrylate neutralizing solution with a Na2SO3 content of 1.00% and a pregelatinized starch content of 1.31% is prepared. UV light curing polymerization is carried out in the same way as in Example 1, and a three-in-one thickener is prepared, and its η, μ% and P% values are measured, and the data are listed in Table 3.
[0037] Example 3
[0038] Weigh 100 g of the above-mentioned basic neutralizing solution, add 2.5 g of 20% aqueous solution of Na2SO3, stir evenly, then add 2.0 g of 10% aqueous solution of hydroxyethyl cellulose (prepare overnight to allow it to fully dissolve), stir evenly, and prepare an alkaline sodium acrylate neutralizing solution with a Na2SO3 content of 1.31% and a hydroxyethyl cellulose content of 0.52%. Perform UV light curing polymerization in the same manner as in Example 1, and prepare a three-in-one thickener, and then prepare a 0.2% aqueous solution, and measure its η, μ% and P% values. The data are listed in Table 3.
[0039] Example 4
[0040] Weigh 100g of the above basic neutralization solution, add 3.0g of 20% Na2SO3 aqueous solution, and stir evenly.
[0041] Then 1.0 g of trehalose was added and stirred to dissolve to prepare a three-in-one sodium acrylate neutralized solution with a Na2SO3 content of 1.57% and a trehalose content of 2.64%. UV light curing polymerization was carried out in the same manner as in Example 1 to prepare a three-in-one thickener, which was then prepared into a 0.2% aqueous solution. Its η, μ% and P% were measured, and the obtained data are listed in Table 3.
[0042] Example 5
[0043] This is a comparative sample. Only 1.57% Na2SO3 was added to the basic neutralizing solution. The process was exactly the same as the previous embodiment. The obtained data are listed in Table 3.
[0044] Table 3 Performance of three-in-one thickener and commercially available sodium polyacrylate thickener (0.2% aqueous solution)
[0045]
[0046]
[0047] From the data in Table 3, it can be seen that (1) the performance (viscosity, salt resistance, and moisturizing performance) of all sodium polyacrylate thickeners containing Na2SO3 systems are better than those of commercially available sodium polyacrylate thickeners. (2) In the (sodium acrylate-Na2SO3) thickener system, the addition of moisturizers has little effect on its original viscosity η. (3) The addition of moisturizers will reduce the μ% value of the three-in-one thickener, that is, the salt resistance is reduced, but its moisturizing performance is significantly improved. Therefore, it is particularly important to find a balance between moisturizing and salt resistance, so that the three-in-one thickener has good moisturizing and salt resistance at the same time.
[0048] (7) Supplementary explanation of performance test
[0049] 1. Viscosity test: using NDJ-1 type rotational viscometer, the rotation speed is 6 rpm (6 revolutions per minute), #2 rotor measurement, the measurement solution concentration is 0.2%;
[0050] 2 Salt resistance test, the viscosity retention rate is μ% to represent its salt resistance, which is defined as
[0051] μ% = n / ηx100%, where η is the viscosity of the aqueous solution at a concentration of 0.2% when no electrolyte salt is added
[0052] n is the viscosity measured after adding 0.15% NaCl salt, so the larger the μ% value, the less the viscosity of the solution decreases after adding salt, and the stronger the salt resistance.
[0053] 3 Moisturizing performance test, the specific determination method is to weigh 30g of double fly powder, add 10g of 0.2% glue solution, stir well, and then put it in a sealed can in a dark place, let it age for 30 minutes, so that the double fly powder can fully absorb the glue, then put the wetted double fly powder micelle on a flat plate with a certain surface area, spread it evenly and press it lightly, weigh its weight m1, place it in a ventilated space with a certain humidity and temperature, and after 48 hours, weigh its weight m2 again. The water retention rate P% of the test sample can be calculated as follows:
[0054] P%=(1-(m1-m2) / m0)x100%
[0055] Where m0 is the water content in the sample. It can be seen that the greater the water retention rate P%, the better the moisturizing performance. However, this is only a relative data, compared with the commercially available sodium polyacrylate thickener and the sample without moisturizer. Because its water retention rate is related to the surface area of the flat plate and the humidity, temperature and ventilation conditions of the storage space, it is just a comparative value.
[0056] In summary: the present invention adopts a simple and easy new method to synthesize a high-viscosity, salt-resistant sodium polyacrylate thickener, and on this basis introduces a humectant to prepare a high-viscosity, salt-resistant and moisturizing three-in-one sodium polyacrylate thickener, thereby broadening its application range.
[0057] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Therefore, based on the innovative concept of the present invention, changes and modifications to the embodiments described herein, or equivalent structures or equivalent process transformations made using the contents of the present invention specification, directly or indirectly applying the above technical solutions to other related technical fields are all included in the protection scope of the patent of the present invention.
Claims
1. A new method for synthesizing a highly viscous and salt-resistant sodium polyacrylate thickener, characterized in that: The following steps are involved: Weigh a certain amount of acrylic acid from which the inhibitor has been removed, add a certain amount of pure water, and then neutralize it with a certain concentration of NaOH solution, slowly add it dropwise, keep the temperature below 40°C, and prepare a sodium acrylate neutralization solution with a neutralization degree of 80% and a solid content of 20% to 45%. Then use sodium sulfite (Na2SO3) and UV light curing technology to polymerize under ultraviolet light to obtain a high-viscosity and salt-resistant sodium polyacrylate thickener.
2. A high-viscosity and salt-resistant sodium polyacrylate thickener, characterized in that: Prepared by the method of claim 1.
3. A method for preparing a three-in-one thickener, characterized in that: The following steps are involved: S1. The alkaline neutralization solution prepared in claim 1 having a neutralization degree of 80%, a solid content of 20% to 45%, and containing Na2SO3 is stirred evenly; then xanthan gum, pregelatinized potato starch, hydroxyethyl cellulose or trehalose are added to prepare a three-in-one sodium acrylate neutralization solution; S2. When the above three-in-one sodium acrylate neutralization solution begins to turn turbid from transparent, take it out and place it directly under a high-pressure mercury lamp, and adjust the distance between the mercury lamp and the sample from far to near. After the reaction is completed, a transparent gel-like three-in-one product is obtained, which is chopped into a 0.2wt% aqueous solution or further granulated, dried at 85°C to constant weight, and then crushed and sieved through 100 mesh or more to obtain a white product, which is the three-in-one thickener.
4. The method for preparing a three-in-one thickener according to claim 3, characterized in that: The amount of Na2SO3 added (calculated on a monomer basis) is 0.1-8.0 wt %, preferably 0.5-5.0 wt %.
5. The method for preparing a three-in-one thickener according to claim 3, characterized in that: The added amount of the xanthan gum, pregelatinized potato starch, hydroxyethyl cellulose or trehalose (calculated on a monomer basis) is 0.2-5.0 wt %, preferably 0.5%-3.0 wt %.
6. A three-in-one thickener, characterized in that: The method is prepared by any one of claims 3 to 5.
Citation Information
Patent Citations
Polymer emulsifying and thickening agent and preparation method thereof
CN104403046A
Production of water-soluble polymer
JP2001040011A
Water-soluble, hydrophobic associating copolymers
US20120129739A1
Cited By
Sodium polyacrylate thickening agent with shear dilution and salt tolerance and preparation method thereof
CN121699054A
A polyacrylic acid sodium thickening agent with shear thinning and salt tolerance and a preparation method thereof
CN121699054B